Advances in clinical chemistry. - Makowski, Gregory S. (Gregory Stephen) (Advances in Clinical Chemistry., 2013)
Advances in Clinical Chemistry contains chapters submitted from experts from academia and clinical laboratory science. Authors are from a diverse field of clinical chemistry disciplines and diagnostics, ranging from basic biochemical exploration to cutting-edge microarray technology.